Regulating high-risk activities in construction industry in Malaysia : the need for legal protection. - Ab Rahman, Rozanah; Hassan, Kamal Halili (Universiti Kebangsaan Malaysia, 2008)
Construction industry is one of the important industries in Malaysia to register positive employment growth. With the progress of the industry, problem of industrial accidents are inevitable due to the nature of work involved in every phase within a construction project. As far as the hazards to the workers' safety is concerned, the high-risk related activities including work at height and lifting operations are identified to have posed its own hazards to the workers that contribute to injury cases in construction. However, there are no specific Regulations and Approved Code of Practice for construction that provide for the provisions to be followed by the duty holder to achieve the general safety duty, particularly for working at height and lifting operations. Thus, the discussion in this article seeks the reference from the regime of occupational safety and health legislation in other jurisdictions that provide for such protection, as a guidance or direction to improve the present legislation on occupational safety and health in Malaysia.